2022
DOI: 10.7759/cureus.26622
|View full text |Cite
|
Sign up to set email alerts
|

A Step Toward the Exploration of Better Spirometric Parameters for Early Diagnosis of Pulmonary Dysfunction in Persons With Type 2 Diabetes Mellitus

Abstract: Objectives: This study aims to determine the forced vital capacity (FVC) and slow vital capacity (SVC) along with other pulmonary functions in Indian diabetic patients for early diagnosis of pulmonary function reduction and to compare the ratios of forced expiratory volume in one second (FEV1) with FVC and SVC (FEV1/FVC and FEV1/SVC) in diabetic patients.Materials and methods: A prospective observational study was carried out in the physiology department for two years after the approval of the institutional et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Comorbidity profiles are a common subject of research in patients with ACO, but in the case of concomitant type 2 diabetes mellitus (T2DM), there is a lack of targeted studies on quality of life, clinical course, and lung function [9][10][11]. In particular, L. Peltola et al found that a higher number of comorbidities had a negative impact on the survival of patients with ACO as well as COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Comorbidity profiles are a common subject of research in patients with ACO, but in the case of concomitant type 2 diabetes mellitus (T2DM), there is a lack of targeted studies on quality of life, clinical course, and lung function [9][10][11]. In particular, L. Peltola et al found that a higher number of comorbidities had a negative impact on the survival of patients with ACO as well as COPD.…”
Section: Introductionmentioning
confidence: 99%